Stress management and Employee performance in Kisoro Hospital, Kisoro District, Uganda - Gregory K.N., Ndongereye (Kabale University, 2020)
Despite the existing techniques and strategies utilized by Kisoro hospital to manage stress, performance among employees has persistently remained low and health workers’ morale to report at work in time has declined which makes delivery of quality health services to patients become poor and insufficient thus adversely affecting their lives (health). The aim of this study was to examine the impact of stress management on employee performance in Kisoro Hospital. Its objectives were: to investigate the relationship between pay and health service delivery in Kisoro Hospital; to analyse factors of stress management techniques and employee performance in Kisoro Hospital; to analyse the effect of pay on the reduction of labour turnover in Kisoro Hospital; to explore whether problem solving can lead to effective health service delivery in Kisoro Hospital. It adopted a case study design and used both qualitative and quantitative approaches to collect data. The target population for this study was 151; however the sampling size that was obtained by stratified and purposive sampling techniques were 60 respondents. The research instruments used included questionnaires, interviews and documentary review. It was found out that effective health service delivery would be good because reasonable pay motivates employees to work towards achieving goals hence improving health service delivery. The study highlighted factors for stress management for effective employee performance. From the findings, 93.3 % of the respondents revealed that giving employees enough time to relax and working in shifts and good working environment and conditions coupled with specific working hours were the most effective ways of managing stress in order to enhance employee performance. It was revealed by 91.7 % of the respondents that if employees are paid well it can help to reduce stress as well as staff turnover thus increasing productivity while 91.67 %revealed that reasonable pay reduces labour turn over in the health sector thus ensuring effective health service delivery. Respondents further brought to the attention of the researcher that employees can perform more effectively when they are given incentives and paid well and in time. Based on the findings it was concluded that pay had a significant relationship with health service delivery. The study also concluded that giving employees enough time to relax and working in shifts and good working environment and conditions coupled with specific working hours were the major factors for stress management and employee performance. Based on the findings the study recommended that, policy makers and government should address the causes of stress among employees such as; by providing adequate remuneration, good relationship at work, paying reasonable salaries and allowances to workers for effective performance in the health sector of Uganda.